Self-Disclosure and Self-Concealment: A Study of User Anonymous Social Behavior from the Perspective of Mimetic Theory——A Case Study of ’momo’ Group on Xiaohongshu - Wang, Sixian (Transactions on Social Science, Education and Humanities Research, 2024)
In the era of the internet, everyone wants to stand out and be seen as unique. Social media accounts have become like virtual ID cards, where people shape their image and show off their personality. However, in an age of increasingly open and transparent information, the challenge of safeguarding user privacy on social media platforms has grown. To meet the demand for anonymous social interaction and emotional expression, a group of users on the platform Xiaohongshu has emerged, taking a contrast approach. They use the same profile pictures and nicknames to hide their identities online, trying to avoid algorithms that track their data. This group, known as "momo," has emerged as a result. This paper, based on Goffman’s dramaturgical theory, uses methods like in-depth interview to observe and analyze the anonymous social behavior of "momo" users. It aims to analyze the underlying motives driving the reconstruction of virtual identities through secondary anonymity, investigating users’ efforts to safeguard their personal social accounts, their current status, and the resulting impacts. Additionally, the study highlights the potential online risks associated with collective psychology and decentralized responsibility within the "momo" community. Hence, both platforms and individuals are urged to enhance their sense of social responsibility and elevate their media literacy to safeguard online security.